VARIABILITY AND CORRELATIVE INTERDEPENDENCE OF RED CLOVER AND ITALIAN RYEGRASS SEED QUALITY DEPENDING ON VARIETIES DURING THE MULTI-YEAR STORAGE PERIOD - Stanisavljević, Rade (Journal on Processing and Energy in Agriculture, 2021)
Seed quality is crucial for achieving the desired number of plants in the mixture, as well as the ratio of grass-legume components. Seeds of red clover and Italian ryegrass can be placed on the market with germination of 70% and more. In this experiment, the seeds of six varieties of red clover and four varieties of Italian lily were examined. Seeds up to four years of age were tested. Seed quality was examined by monitoring the following parameters: germination energy, amount of hard-dormant seed, total germination and amount of abnormal seedlings. The tested varieties of red clover and Italian ryegrass seeds showed the best quality after one and two years of storage. After four years of storing seeds, out of six tested varieties of red clover, two did not meet the criteria for marketing in Serbia, according to the current rulebook on seed quality. In the case of Italian ryegrass, out of four tested varieties, two did not meet the criteria for placing seeds on the market.